ANALISIS FINANCIAL DISTRESS DENGAN MENGGUNAKAN MODEL GROVER PADA PT. HERO SUPERMARKET TBK. PERIODE 2015-2022 - Amalia, Luthfi Thoriq; Manda, Gusganda Suria (STIE Mahardhika, 2025)
The retail industry is one of the business sectors affected by the progress of the industrial revolution 4.0. PT Hero Supermarket Tbk is one of the companies facing a decline in revenue and occurs continuously to close 26 stores and lay off 532 employees in early January 2019. The purpose of this research is to analyze financial distress at PT Hero Supermarket Tbk. The approach used in this research is quantitative research with descriptive analysis by describing and explaining something that is studied in accordance with the actual situation, and citing conclusions from phenomena that can be observed through numbers. The data applied in this study is secondary data. The data source in this study is the financial statements of PT Hero Supermakrket Tbk. This study uses the Grover model analysis technique (G-Score). The results of this study show that PT Hero Supermarket Tbk faced financial distress conditions in 2018, 2020, 2021 and 2022. And faced safe conditions in 2015, 2016, 2017, and 2019.